2011
DOI: 10.4021/wjon390e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided Central Venous Catheterization for Home Parenteral Nutrition and Hydratation in Advanced Incurable Cancer Patients: Results of A Prospective Observational Study

Abstract: BackgroundMost patients with advanced cancer are frequently malnourished and frequently they develop decreased oral fluid intake and dehidratation. Home parenteral nutrition (HPN) is an increasingly used therapy for patients with advanced cancer. A central venous access device is often an essential component allowing parenteral nutrition and hidratation. However central venous catheter (CVC) insertion represents a risk for pneumothorax or other mechanical complications. This study aimed to determine the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A paper studying PORTs was excluded due to the administration of chemotherapy in a palliative care setting [19]. Hence, a total of five publications were included with four studies on PICCs [20][21][22][23] and one study on central lines [24]. The inter-rater reliability of publication screening by the authors was 97.6%, which was related to the doubtful eligibility of one publication, resolved by consensus.…”
Section: Search Strategy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper studying PORTs was excluded due to the administration of chemotherapy in a palliative care setting [19]. Hence, a total of five publications were included with four studies on PICCs [20][21][22][23] and one study on central lines [24]. The inter-rater reliability of publication screening by the authors was 97.6%, which was related to the doubtful eligibility of one publication, resolved by consensus.…”
Section: Search Strategy Resultsmentioning
confidence: 99%
“…The characteristics of 327 patients analyzed in this meta-analysis are shown in Table 2. Regarding the type of CVAD, 207 patients who received central line insertion were contributed by a single study, and the remaining 120 patients who had PICCs inserted were from the remaining four publications [20][21][22][23][24]. There was a total of 209 central line insertions in 207 patients due to 2 failed insertions [24].…”
Section: Baseline Patient Characteristicsmentioning
confidence: 99%
“…The procedure was performed using Esaote SpA equipped with two transducers between 3.5 to 7.5 MHZ, with a needle guide. The method that we commonly use is 'the three-handed method', as previously reported (17,18); this method requires an assistant to hold the probe, while the operator controls the needle and performs the procedure under real-time guidance, and the nurse helps the two physicians during the maneuver. The central vein was identified along its greater longitudinal axis and its relationship with other anatomical structures using Valsalva's maneuver which determines an increase of the diameter of the veins.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical complications of CVC insertion without ultrasound (US) guidance, such as arterial puncture and pneumothorax, are seen in up to 21% of attempts, and up to 35% of insertion attempts are not successful (3)(4)(5). Prior researches show that the use of US-guide CVC has been associated with a reduction in complication rate and an improved first-pass success when placing CVC in the internal jugular vein (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). We sought to investigate within US-guidance CVC in a subset of cancer patients with severe thrombocytopenia also effects the safety, reducing bleeding complications and avoid prophylactic platelet transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalized COVID-19 patients often need vascular devices for the delivery of fluids, parenteral nutrition, medication, phlebotomy, and to avoid multiple venipuncture attempts [ 5 , 6 ]. A previous study by the authors reported the results of 1,978 ultrasound-guided central venous catheter (CVC) insertional procedures [ 7 ], and the authors previously published the results of a study on ultrasound-guided central venous catheterization for home parenteral nutrition and hydration in 207 advanced-stage cancer patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%